Cambarus (C.) appalachiensis, a new species of crayfish (Decapoda: Cambaridae) from the New River Basin of Virginia and West Virginia, USA - Loughman, Zachary J.; Welsh, Stuart A.; Thoma, Roger F. (Zootaxa, 2017)
Cambarus (Cambarus) appalachiensis is a stream-dwelling crayfish endemic to the greater New River basins of Virginia and West Virginia. The new species is morphologically most similar to Cambarus sciotensis. Cambarus appalachiensis can be differentiated from C. sciotensis by its more elongated chelae which possess a single mesial row of tubercles, reduced to no tuberculation on the dorsal-longitudinal ridge of the dactyl, and reduced lateral impression. Cambarus sciotensis has a more subrectangular chelae with two rows of mesial margin tubercles on the chelae, as well as both a pronounced dorsal-longitudinal ridge and pronounced lateral impression. Several chelae meristic ratios also differentiate C. appalachiensis from C. sciotensis. Within the New, Gauley, and lower portions of the Greenbrier basins C. appalachiensis is the dominant tertiary burrowing Cambarus species, and as such, is considered stable across its range.